Experimental Study on the Influence of Moisture Content on the Mechanical Properties of Coal - Mingxing Gao; Yongli Liu (Geofluids)
Water injection in coal seams will lead to the increase of moisture content in coal, which plays an essential role in the physical and mechanical properties of coal. In order to study the influence of moisture content on the mechanical properties of soft media, the forming pressure (20 MPa) and particle size ratio (0-1 mm (50%), 1-2 mm (25%), and 2-3 mm (25%)) during briquette preparation were firstly determined in this paper. Briquettes with different moisture contents (3%, 6%, 9%, 12%, and 15%) were prepared by using self-developed briquettes. Uniaxial and triaxial compression tests were carried out using the RMT-150C rock mechanics test system. The results show that the uniaxial compressive strength and elastic modulus of briquette samples increase first and then decrease with the increase of briquette water, while Poisson’s ratio decreases first and then increases with the increase of briquette water. When the moisture content is around 9%, the maximum uniaxial compressive strength is 0.866 MPa, the maximum elastic modulus is 1.385 GPa, and Poisson’s ratio is at the minimum of 0.259. The compressive strength of briquettes increases with the increase of confining pressure. With the increase of moisture content, the cohesion and internal friction angle of briquettes first increased and then decreased.